GLOBAL ECONOMIC POLICY IN AN ERA OF UNCERTAINTY - Silvia Ekasari; Mohamad Khairi Bin Haji Othman (Adisam Publisher, 2025)
Global uncertainties triggered by geopolitical dynamics, economic crises, climate change, pandemics, and technological transformation affect the stability of the world economy. Economic policy in this era requires a flexible, adaptive approach based on multilateral collaboration. Cooperation between global institutions and strengthening domestic policies are key strategies to address supply chain disruptions, trade imbalances, and fiscal challenges. Amidst uncertainty, policies based on solidarity, innovation, and sustainability can create a more inclusive and resilient economic stability. This proactive approach is expected to anticipate future challenges while promoting sustainable global economic growth.